A review of informal volunteerism in emergencies and disasters: Definition, opportunities and challenges. (September 2015) - Whittaker, Joshua; McLennan, Blythe; Handmer, John
Abstract: Despite highly specialised and capable emergency management systems, ordinary citizens are usually first on the scene in an emergency or disaster, and remain long after official services have ceased. Citizens often play vital roles in helping those affected to respond and recover, and can provide invaluable assistance to official agencies. However, in most developed countries, emergency and disaster management relies largely on a workforce of professionals and, to varying degrees, volunteers affiliated with official agencies. Those who work outside of such systems have tended to be viewed as a nuisance or liability, and their efforts are often undervalued. Given increasing disaster risk worldwide due to population growth, urban development and climate change, it is likely that 'informal' volunteers will provide much of the additional surge capacity required to respond to more frequent emergencies and disasters in the future. This paper considers the role of informal volunteers in emergency and disaster management. Definitions of volunteerism are reviewed and it is argued that there is an overemphasis on volunteering within, and for, state and formal organisations. We offer a broader definition of 'informal volunteerism' that recognises the many ways ordinary citizens volunteer their time, knowledge, skills and resources to help others in times of crisis. Two broad types of informal volunteerism are identified – emergent and extending – and the implications for emergency and disaster management are considered. Particular attention is given to increasing 'digital volunteerism' due to the greater accessibility of sophisticated but simple information and communication technologies. Culture and legal liability are identified as key barriers to greater participation of informal volunteers. We argue that more adaptive and inclusive models of emergency and disaster management are needed to harness the capacities and resilience that exist within and across communities.